PRODUCT DIFFERENTIATION AND DIGITAL PROMOTION IN A BAKSO RUSUK MICROENTERPRISE IN KONAWE - Melati Melati (Universitas Prof. Dr. Hazairin SH, 2026)
This study analyzes the marketing strategy of a Bakso Rusuk culinary microenterprise in Konawe Regency by treating product differentiation and digital promotion as integrated practices for building market positioning. The qualitative case study used an in-depth interview with the owner, two to three hours of direct observation during operating hours, and field notes; the data were analyzed descriptively through thematic organization. Market appeal was shaped by the distinctiveness of beef-rib meatballs, the use of Instagram, Facebook, and WhatsApp, affordable pricing, friendly and quick service, and local ingredients and labor. The study's novelty lies in explaining how local product identity, digital communication, service quality, and locally embedded resources operate as a configuration in a regional culinary microenterprise. Theoretically, differentiation and digital promotion are mutually reinforcing rather than separate practices. Practically, owners should clarify product identity, highlight visual uniqueness, strengthen customer relationships through WhatsApp, and communicate local value consistently.